Effect of Job Embeddedness on Job Satisfaction and Intention to Leave - Menon, R. Greeshma (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the study is to test the relationship between job embeddedness_ job satisfaction, job satisfaction _ intention to leave, job embeddedness _ intention to leave of an ITES employees working in various IT sectors in Chennai. Totally 147 Samples were selected for the study. The sample included 103 males, 44 females. The sample has 22 managers and 125non-managers. Data were collected through structured questionnaire using global scales. The data were examined using Partial Least Square (Smart PLS), to test the proposed relationships among the variables. The result of the study indicates that Job Embeddedness is positively related with job satisfaction and negatively related with intention to leave. Job satisfaction is negatively related with intention to leave.